Prevention or treatment: The benefits of Trichomonas vaginalis vaccine - Sarah L. Cudmore; Gary E. Garber (Elsevier, 2010)
Summary: Trichomoniasis (infection with Trichomonas vaginalis) is the most common non-viral sexually transmitted disease (STI) in the world. Although treatment is available, most cases occur in developing countries, where accessing healthcare is difficult and facilities are limited. Additionally, infection is often asymptomatic and as such goes untreated, creating reservoirs of T. vaginalis that allow the disease to spread within the community. Because of this there has been little success in controlling the incidence of trichomoniasis, especially amongst the underprivileged. The development of a vaccine against T. vaginalis could reduce the human costs (pregnancy complications, infertility), medical costs (repeated doctor visits, increased susceptibility to human immunodeficiency virus (HIV) infection), and societal costs (stigma of STI, cycles of untreated infection) associated with trichomoniasis. Keywords: Trichomonas vaginalis, Trichomoniasis, Vaccination, STI, HIV